Creative darts, draping, frills and flounces, collars, necklines and sleeves, trousers and skirts - Brambatti, Manuela (Promopress, 2020)
"The third book from this series on illustration and design focuses on the most popular accessories: shoes, handbags, hats, belts, gloves and glasses. Brilliantly illustrated by Manuela Brambatti, a key member of the Gianni Versace fashion house for nearly thirty years, and with the participation of the designer Fabio Menconi (senior designer for Escada and Armani, among others), the book guides readers through the fashion world's most iconic accessories, and it features practical information and technical advice on how to draw them to achieve a desired result. From creating a basic drawing to using color, the way in which techniques are presented seeks to encourage readers to try out what they have learned. The publication provides detailed information on how to capture different materials, surfaces and decorations--for example, skin, natural fibers, wool and prints--and it includes sections that provide tips on where to look for inspiration. It also offers examples of transformations in designs and reviews the historical development of accessories. In short, this is a comprehensive, structured and systematic volume that will serve professionals, students and anyone who wants to venture into designing and illustrating fashion accessories."